The bull and bear market model of Huang and Day : Some extensions and new results - Fabio Tramontana; Frank Westerhoff; Laura Gardini (Bamberg University, Bamberg Economic Research Group (BERG), 2012)
We develop a financial market model with interacting chartists and fundamentalists that embeds the famous bull and bear market model of Huang and Day as a special case. Their model is given by a one-dimensional continuous piecewise-linear map. Our model, on the other hand, is more flexible and is represented by a one-dimensional discontinuous piecewise-linear map. Nevertheless, we are able to provide a more or less complete analytical treatment of the model dynamics by characterizing its possible outcomes in parameter space. In addition, we show that quite different scenarios can trigger real-world phenomena such as bull and bear market dynamics and excess volatility.
Keywords: 330; Heterogeneous interacting agents; Bull and bear market dynamics; Piecewise-linear maps; Border collision bifurcations; Aktienmarkt; Anlageverhalten; Wertpapierspekulation; Börsenkurs; Volatilität; Theorie